LARANGAN MELAUT PADA HARI JUM’AT DI DESA SINGKUANG DITINJAU DARI PERSPKTIF MAQASID SYARI’AH - Hendra Gunawan MA (IAIN Padangsidimpuan, 2022)
This paper explains the prohibition of going to sea on Fridays in Singkuang village from the perspective of maqasid sharia, because basically fishing activity is a suggestion from Allah SWT to meet the needs of human life, fulfill the nutrition of children's growth. However, in the village of Singkuang, a Village Regulation (Perdes) regarding the Prohibition of Fishing on Fridays appeared.The question here is what is the background, objectives, formulation of sanctions, and the implementation of the Village Regulation on the Prohibition of Going to Sea on Fridays, and how it is viewed from the perspective of maqasid sharia.This research is a qualitative research, where the author uses data collection methods with observations and interviews with local people regarding the prohibition of going to sea on Fridays, then the data is analyzed with the concept of maqasid sharia.The findings in this study, that the prohibition to go to sea on Fridays was motivated by the number of fishermen in Singkuang village who neglected Friday prayers due to fishing, this is according to the belief of the local community if left unchecked will be able to invite harm (disaster) to the village, then According to the local community, this village regulation was made to remind fishermen to perform Friday prayers. This prohibition from going to sea when viewed from the perspective of maqasid sharia is very relevant, namely to maintain worship.